Mapping the global landscape of Malaysia's microbusinesses and mobile payments - Mustapha, Musramaini; Awang Kader, Mohd Aidil Riduan; Ghazali, Mohd Samsuri; Ab Malik, Ariff Md (GADING Journal for the Social Sciences, 2024)
Microenterprises constitute over ninety percent of the overall total enterprises in Malaysia. Descriptive metadata and scientometric analysis were utilised to examine the research and development studies of microbusinesses and mobile payment systems in Malaysia. Literature patterns and research development trends pertaining to mobile payments and microbusinesses were evaluated by considering a compilation of more than 8,414 relevant articles. Hence, the objective of this study is to identify current trends in mobile payment and microbusiness research and publication in Malaysia, as well as trend research subjects that have been highlighted across the literature over time. Utilising the Web of Science database, publication trends, a list of authors, journals and affiliations, actively participating countries, top keywords, research clusters, and the top references with the most pronounced citation bursts were identified, compiled, and generated for the study. In total, 118 countries or states were identified as having published pertinent information regarding microbusinesses and mobile payments in Malaysia. Additionally, this study found a gradual increase in the number of publications, with England producing the most, followed by the United States and China. In Malaysia, a collective of 6,913 authors were recognised for their contributions to the fields of microbusiness in Malaysia and mobile payment studies. This study examines the mobile payment trend among Malaysia’s microbusinesses in the cluster, including those in the business cycle, corporate social responsibility, and innovation. It is observed that microbusiness publications in Malaysia place greater emphasis on empirical investigation and mobile services in relation to mobile payment.